Exploring the Impact of Resveratrol on Gynecological Cancer: Insights and Perspectives - Revathi, Unni K; Amrisa, Pavithra; Aparna, Kumar G; Santhy, K S (Plant Science Today, 2023)
Gynecological cancers, a group of malignancies affecting the female reproductive system, are a significant cause of morbidity and mortality in women. Different types of gynecological cancers differ by distinct attributes, risk determinants, and therapeutic methodologies. So, depending on the type and stage of the cancer, a tailored combination of therapies is required for the treatment. However, it is shocking that the side effects of these therapeutic methods range from mild to severe. Hence, developing innovative therapeutic approaches to improve patient outcomes is imperative. Here's the juncture where the role of plant-derived compounds in curing gynecological cancers becomes evident. Various plant-derived compounds, including phytochemicals, polyphenols, alkaloids, and terpenoids for their cytotoxic, apoptotic, anti-angiogenic, and immunomodulatory properties, have been examined so far. Besides, certain phytocompounds can modulate hormonal-dependent gynecological cancers. Among the widely studied phytocompounds, RSV is the one that is extensively researched in vitro, in vivo and in-silico studies. In this context, this review article provides insights into the present-day knowledge about how RSV can potentially manage gynecological cancers. However, further research is needed to standardize their mode of action, optimal dosages, and potential interactions with conventional treatments. Rigorous clinical trials must validate their safety and efficacy profiles in different patient populations. As a result, a novel avenue for treating and preventing gynecological cancers could emerge by harnessing the multifaceted properties of phyto compounds, instilling new hope for patients and healthcare providers alike.